Systemic Review Of Parkinson’s Disease In Purview Of Kampavata - Shukla, Ragini; Sharma, Jitendra Kumar; Sharma, Purushottam Das; Sharma, Dinesh Kumar; Deepa (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is the eternal splendid science of medicine because it deals with all aspects of life, especially of human being science time immemorial. The Parkinson’s disease (Kampavata) is a progressive neurodegenerative disorder. The disease affects approximately 2 out of 1000 people, and most often develops after age of fifty, the clinical course is chronic and progressive with severe disability attained after ten years. According to Ayurveda, Kampavata is a Nanatmaja disorder of Vata. The Parkinson’s disease is a slowly progressive disease of late adult life and is one of the most prevalent neurological disorders. There is no cure for Parkinson’s disease, but medications and multidisciplinary management can provide relief from the symptoms. For the treatment of Parkinson’s disease there are numerous drugs used by modern medicinal system but only L Dopa has better results in addition numerous Ayurvedic drugs which has similar compounds are useful in this grave disease. This manuscript construct for the absolute information about the Parkinson’s disease (Kampavata) the main headings like etiopathogenesis, feature functions in conjunction with specific treatments for the remedy of those ailments.